Mapping resistance to the bird cherry-oat aphid and the greenbug in wheat using sequence-based genotyping - Crespo-Herrera, L. A.; Akhunov, Eduard D.; Garkava-Gustavsson, L.; Jordan, Katherine W.; Smith, C. Michael; Singh, R. P.; Åhman, I. (My University, 2014)
The aphids Rhopalosiphum padi and Schizaphis graminum are important pests of common wheat (Triticum aestivum L.). Characterization of the genetic bases of resistance sources is crucial to facilitate the development of resistant wheat cultivars to these insects. We examined 140 recombinant inbred lines (RILs) from the cross of the susceptible wheat Seri M82 with the synthetic hexaploid wheat CWI76364, resistant to both aphid species. The RILs were phenotyped for R. padi antibiosis and tolerance traits. Phenotyping of S. graminum resistance was based on leaf chlorosis in a greenhouse screening, and also on the number of S. graminum per tiller in a field trial. Seedling pubescence was scored in each RIL. Using a sequence-based genotyping method we located genomic regions associated to these resistance traits. One QTL for R. padi antibiosis was found in chromosome 4BL; it explained 10.2% of phenotypic variation and was located 14.6 cM apart from the pubescence locus. However, we did not find any association between plant pubescence and the other resistance traits. We found two QTLs for tolerance to R. padi in chromosomes 5AL and 5BL, with an epistatic interaction between a locus in chromosome 3AL and the tolerance QTL in 5AL. These genomic regions together explained about 35% of the phenotypic variation. We confirmed the location of a previously reported gene for S. graminum resistance (Gba) in 7DL and found an additional, novel QTL associated with the number of aphids per tiller in chromosome 2DL. This is the first report where resistance to R. padi in wheat is mapped and also where chromosome 2DL shown to be associated with S. graminum resistance.
Citation: Crespo-Herrera, L. A., Akhunov, E., Garkava-Gustavsson, L., Jordan, K. W., Smith, C. M., Singh, R. P., & Åhman, I. (2014). Mapping resistance to the bird cherry-oat aphid and the greenbug in wheat using sequence-based genotyping. Theoretical and Applied Genetics, 127(9), 1963-1973.
Keywords: Rhopalosiphum padi; Schizaphis graminum; synthetic hexaploid wheat; genotyping by sequencing; Resistance; QTLs